2018
DOI: 10.17072/2218-9173-2018-3-396-418
|View full text |Cite
|
Sign up to set email alerts
|

Migration Factors in the Arctic Zone of the Russian Federation

Abstract: Институт экономики Уральского отделения Российской академии наук, г. Екатеринбург, Россия Л. В. ВОРОНИНА Федеральный исследовательский центр комплексного изучения Арктики имени академика Н. П. Лаверова Российской академии наук, г. Архангельск, Россия Е. В. СМИРЕННИКОВА Федеральный исследовательский центр комплексного изучения Арктики имени академика Н. П. Лаверова Российской академии наук, г. Архангельск, Россия А. В. УХАНОВА Федеральный исследовательский центр комплексного изучения Арктики имени академика Н. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Over 70% of those interviewed confirmed that one of the critical drivers of emigration is insufficient housing and educational infrastructure: "All housing is old", "Houses are almost destroyed"; "Most buildings need capital repair"; "They lack central heating, hot and cold water, electricity in the houses." However, we disagree with Shelomentsev (2018), et al [27], who noticed that the most significant factor impacting migration outflow in YNAO is "price of houses". This factor was not mentioned by any of our respondents, they primarily worried about bad conditions, and the lack of modern conveniences in the houses.…”
Section: "Push" Factors Of Migration Outflow In Ynao: the Survey Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Over 70% of those interviewed confirmed that one of the critical drivers of emigration is insufficient housing and educational infrastructure: "All housing is old", "Houses are almost destroyed"; "Most buildings need capital repair"; "They lack central heating, hot and cold water, electricity in the houses." However, we disagree with Shelomentsev (2018), et al [27], who noticed that the most significant factor impacting migration outflow in YNAO is "price of houses". This factor was not mentioned by any of our respondents, they primarily worried about bad conditions, and the lack of modern conveniences in the houses.…”
Section: "Push" Factors Of Migration Outflow In Ynao: the Survey Resultscontrasting
confidence: 99%
“…In 2016, a survey of the Arctic regions' residents showed that one of the significant reasons for outmigration in the Russian Arctic was the "insecure criminal situation" (yield was 17.4%) [96]. However, Shelomentsev (2018), et al [27] considered this data to be unreliable and considered that geopolitical factors did not have a relevant impact on migration expectations of the Arctic population.…”
Section: "Push" Factors Of Migration Outflow In Ynao: the Survey Resultsmentioning
confidence: 99%
See 1 more Smart Citation